2020
DOI: 10.1002/csc2.20319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of durum wheat lines derived from interspecific crosses under drought and heat stress

Abstract: The productivity of durum wheat [Triticum turgidum subsp. durum (Desf.) van Slageren] is affected by drought and/or high temperatures, challenges to be amplified by climate change. Pre‐breeding using wild relatives can supply useful traits for durum wheat improvement to adapt to major abiotic and biotic stresses. Sixty‐seven lines issued from backcrosses of Cham5 and Haurani durum wheat varieties with accessions of Triticum aegilopoides (Link) Bal. ex Koern., T. dicoccoides Koern. ex Schweinf., T. urartu Thuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
5
23
0
Order By: Relevance
“…However, it is worth noting that Ae. speltoides may be a good source of tolerance to drought, as reported by Waines [44] and Aberkane et al [45].…”
Section: Variance and Ammi Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…However, it is worth noting that Ae. speltoides may be a good source of tolerance to drought, as reported by Waines [44] and Aberkane et al [45].…”
Section: Variance and Ammi Analysismentioning
confidence: 61%
“…As reported by Zaïm et al [30], here, simple top crosses of three wild relative species with old ICARDA varieties followed by targeted field selection did not appear to result in any negative effect; rather, it delivered a large genetic gain in productivity. Aberkane et al [45] also found that the wild relative-derived lines, (Haurani*2/Triticum urartu) and (Cham5*2/T. dicoccoides), yielded, respectively, 196 and 142% of their recurrent parents' yield under drought stress.…”
Section: Performance Of Grain Yield and Stability Of Genotypesmentioning
confidence: 96%
“…For instance, line 142001, derived from T. Urartu, had significantly higher BLUPs associated with higher stability, according to both Bi and S 2 di. The same line showed a yield increase under drought stress, combined with earliness and cooler canopy under heat stress [77,85]. Under favorable conditions, some Haurani derivatives (142064 for example) can yield twice as much as the recurrent parent, which indicates a high contribution to yield potential.…”
Section: Impact Of Wild Relatives On Yield Potentialmentioning
confidence: 87%
“…The testing environments exposed durum wheat to favorable conditions, drought, and heat stresses, in addition to disease pressure, mainly leaf rust at Allal Tazi and tan spot at Annoceur. In addition, the contrasting environments at Tessaout and Melk Zher showed their effectiveness to select for drought tolerance [77]. The genetic correlation showed that some genotypes can be selected simultaneously for drought and heat tolerance.…”
Section: Dissection Of the Genotype By Environment Interactionmentioning
confidence: 99%
“…com/carrot-stress-tolerance-and-wild-relative-breedingwith-dr-simon-philipp). Aberkane et al (2021), in "Evaluation of durum wheat lines derived from interspecific crosses under drought and heat stress," conclude that gene introgression from wild diploid and wild tetraploid wheat-derived materials pays off and can increase wheat resilience. Drought tolerant genotypes with high values of relative chlorophyll content and more green leaves at maturity have been identified by Ochieng et al (2021), in "Novel sources of drought tolerance from landraces and wild sorghum relatives".…”
mentioning
confidence: 99%